Functional features of paralinguistic tools in English communication - Raximova Nargiza Ulugbekovna; Abduazizova D.A (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
Paralinguistic tools encompass non-verbal elements such as tone, pitch, volume, intonation, pauses, facial expressions, gestures, and body language that accompany spoken words to enhance communication. In English communication, these features play a crucial role in conveying emotions, clarifying intentions, emphasizing meaning, and regulating conversational flow. This article explores the functional aspects of these tools, highlighting their importance in everyday interactions, professional settings, and intercultural contexts. Through qualitative analysis of spoken English corpora, including dialogues from interviews, TED Talks, and media, the study demonstrates how paralinguistics enrich verbal messages, foster mutual understanding, and prevent misinterpretations. The research also draws comparisons with Uzbek linguistic perspectives to provide a cross-cultural dimension, emphasizing the multimodal nature of language. Findings suggest that proficiency in paralinguistic cues is essential for effective English communication, particularly for non-native speakers, and recommends integrating them into language education programs.